Pre-Generation of Student Module in Intelligent Tutoring System - Ali, Safdar (2009)
An intelligent tutoring system (ITS) is a system that provides direct modified instruction or feedback to students without the interference of human beings. Most of the researches in ITS have been in assessment, reforming of the learning objects and change of the learning object finding path. To make an ITS as efficient as expert human tutors, this research aims at identifying the user understanding level of a user prior to using an ITS by conducting a pre-test. Upon completing the test, user will be presented with a teaching session that is based on his/her performance in the undertaken pre-test. The system is intended for undergraduate students to learn knowledge representation. Two systems were developed for the purpose of evaluation and namely Version A and Version B. Version A adopts the existing approach that assumes all students have the same background knowledge, while Version B conducted the teaching session according to students existing knowledge. A pilot test was performed on the BIT undergraduate students. The results showed that by using Version B, students obtained a better result compared to using Version A.